Design of a Culinary Arts Gallery in Binjai City with a Tropical Architectural Approach - Habibah Azzahra Hasibuan; Nelson Manumpak Siahaan (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The planning for a Culinary Arts Gallery in Binjai City is intended as a forum for culinary and cultural diversity in Binjai City to be better known and developed. Binjai City is a city with various ethnicities and cultures in it. This cultural diversity comes from the city's residents, including tribes; Malay, Toba Batak, Karo, Chinese, Javanese, and other tribes. The cultural diversity of the city of Binjai has resulted in the growth of various cultural characteristics in the form of culinary specialties in the city of Binjai such as tau kua heci and Binjai's typical rambutan cake which gives the city its identity. Furthermore, the cultural and culinary diversity of the city of Binjai has the potential to be developed in terms of economics and tourism. Therefore, it is necessary to have a planning study for a Culinary Arts Gallery in Binjai City that can accommodate the culinary arts of Binjai City so that it is easier to introduce it to the wider community in the form of a Culinary Arts Gallery. This plan is intended to accommodate culinary activities and functions as a forum for arts and cultural activities for the people of Binjai City.